2019
DOI: 10.17219/acem/94146
|View full text |Cite
|
Sign up to set email alerts
|

Patient awareness, perception and attitude to contrast-enhanced CT examination: Implications for communication and compliance with patients’ preferences

Abstract: Background. Despite the high volume of contrast-enhanced computed tomography (CECT) examinations, there is limited awareness about its risks among patients and little is known about the influence of patient information sheets. Objectives. The objective of this study was to assess patients' awareness and perception of risks related to CECT examination and how they are influenced by an information sheet. Material and methods. A total of 263 adult patients scheduled for a CECT examination completed a questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
(28 reference statements)
0
8
0
1
Order By: Relevance
“…Particular attention should be paid to such patients, as previous studies have shown that first-time examinations are associated with higher anxiety levels. 4,5,8,65,72,75,76,78 The CCTA process times between the groups were similar. In a previous study, 360 VR exerted a positive effect on the time required to perform a chest radiography, 51,52 which usually has a shorter process time than CCTA.…”
Section: Discussionmentioning
confidence: 78%
“…Particular attention should be paid to such patients, as previous studies have shown that first-time examinations are associated with higher anxiety levels. 4,5,8,65,72,75,76,78 The CCTA process times between the groups were similar. In a previous study, 360 VR exerted a positive effect on the time required to perform a chest radiography, 51,52 which usually has a shorter process time than CCTA.…”
Section: Discussionmentioning
confidence: 78%
“…[11][12][13][14][15][16] In particular, patients' knowledge about medical radiation is limited, and the perception of radiation risks is variable depending on age and educational level. [17][18][19] In Italy, this issue is of special interest owing to the European Council Directive 2013/59/ Euratom having become effective starting on August 27, 2020. 11,20 In this context, a nationwide survey might help to more thoroughly assess patients' knowledge about medical radiation and its potential risks.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, CTUs to investigate haematuria make up 2.3% and 5.2% of each hospitals overall respective workload in the CT department. Further reductions in the number of CTUs performed would be a welcome reduction in workload for the radiology department as well sparing the patient the potential harmful sequela of a contrast enhanced scan of which they are often unaware [9].…”
Section: Discussionmentioning
confidence: 99%